Public expenditures, innovation and economic growth: Empirical evidence from G20 countries - Horst Hanusch; Lekha Chakraborty; Swati Khurana (Universität Augsburg, Institut für Volkswirtschaftslehre, 2016)
The paper examines public expenditures and their effects on economic growth. For that purpose we choose four categories of expenditures, defence, infrastructure, human capital and R & D expenditures. Behind these expenditures stands, in socio-political consideration, a certain notion of the state as an active provider of public services for different purposes. From an analytical perspective the state is integrated in an institutional or sectoral framework which consists of the public, the financial and the real sector. All of these parts are oriented towards the development of an economy like it is formulated in the concept of "Comprehensive Neo-Schumpeterian Economics" (CNSE). In such a framework the state offers in the first case via defence expenditures national security as a pure public good which may have severe effects on the economic situation of an economy. In the second case the state provides capital investment as a prerequisite for economic development. In the third instance the state is defined as an institution preparing individuals and society for the uncertainties to come (resilience). The fourth category is closely related to innovation, hence traditionally R & D expenditures are taken as a proxy for the propensity of a firm or a society to invest into the future by creating novelties and using them as innovations. So, which kind of state is the most relevant one when we focus on economic growth and development? Is it the "security state" or the "development state", in the sense of catching up, which matters most? What role plays a state which focusses on resilience by stressing education and health (human capital) of its citizens in order to master the future? Or is it, last but not least, the "innovation oriented state", focussing on R & D, which has the biggest influence on economic growth? To answer these questions we investigate the links between the four categories of public expenditures and economic growth in an empirical panel data regression model using data for the G20 countries during the period between 2000 and 2012 within the constraints of data availability. The results reveal that the impact of innovation oriented spending on economic growth is much higher than that of the variables. The data used stems from the electronic data base of Government Finance Statistics (IMF), the Infrastructure Reports for the G20 countries and the World Development Indicators (World Bank).
urn:nbn:de:bvb:384-opus4-710795
Keywords: O30; O38; H5; 330; Public Expenditure; Innovation; Growth; Neo-Schumpeterian Economics